2018
DOI: 10.1111/famp.12371
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Synchrony During Verbal Interaction in Romantic Relationships

Abstract: Previous studies about romantic relationships have shown that the reciprocal influence between partners occurs not only at the behavioral and socio-emotional levels, but also at the psychophysiological level. This reciprocal influence is expressed in a pattern of physiological synchrony between partners (i.e., coordinated dynamics of the physiological time series). The main aim of the present study was to explore the presence of a pattern of physiological synchrony in electrodermal activity (EDA) during a coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 63 publications
3
62
1
Order By: Relevance
“…Palmieri et al (2018) found higher EDA synchrony in clinical interviews when the interviewer had received a secure-attachment prime. Coutinho et al (2018) supported the significant synchrony findings in a sample of romantic couples, yet not with the concordance index but with the cross-correlational method of surrogate synchrony (concordance and surrogate synchrony are introduced in the methods section below).…”
Section: Research On Physiological Synchrony In Psychotherapy and Psymentioning
confidence: 93%
“…Palmieri et al (2018) found higher EDA synchrony in clinical interviews when the interviewer had received a secure-attachment prime. Coutinho et al (2018) supported the significant synchrony findings in a sample of romantic couples, yet not with the concordance index but with the cross-correlational method of surrogate synchrony (concordance and surrogate synchrony are introduced in the methods section below).…”
Section: Research On Physiological Synchrony In Psychotherapy and Psymentioning
confidence: 93%
“…The function of physiological synchrony in positive as opposed to negative emotional states remains uncertain. There is naivete in the assumption that synchrony is only commonly associated with positive emotional states [11,[15][16][17][18] as numerous contradictory findings challenge the generality of this principle [19][20][21][22]. For instance, events that precipitate negative emotional states, such as couple conflict, have been found to synchronize HRV and to elevate inflammatory compounds [19].…”
Section: Introductionmentioning
confidence: 99%
“…Physiological synchrony during such conflicts have also predicted marital dissatisfaction [20]. Similarly, synchrony of electrodermal activity (EDA), the difference in electrical potential between different areas of the skin, was enhanced during negative rather than positive interactions between romantic partners [21]. Relatedly, among dyadic peers, physiological synchrony has been observed to be heightened during social interactions that involve partners who disliked each other [23].…”
Section: Introductionmentioning
confidence: 99%
“…Each participant watched a set of video-vignettes of his/her romantic partner expressing emotional contents, and was asked to, while watching, either focus on his/her own experience (self condition) or his/her partner's experience (other condition). These video-vignettes of 20 s duration containing the expression of positive and negative emotional contents were extracted from a previously video-recorded interaction task performed in the lab, where participants shared things that they either liked (positive videos) or disliked (negative videos) about their partner (more details regarding the interaction task can be found in Coutinho et al, 2017Coutinho et al, , 2018).…”
Section: Experimental Taskmentioning
confidence: 99%